Co‐assembled Monolayers as Hole‐Selective Contact for High‐Performance Inverted Perovskite Solar Cells with Optimized Recombination Loss and Long‐Term Stability. (9th June 2022) - Deng, Xiang; Qi, Feng; Li, Fengzhu; Wu, Shengfan; Lin, Francis R.; Zhang, Zhuomin; Guan, Zhiqiang; Yang, Zhengbao; Lee, Chun‐Sing; Jen, Alex K.‐Y.
Abstract: Self‐assembled monolayers (SAMs) have been widely employed as an effective way to modify interfaces of electronic/optoelectronic devices. To achieve a good control of the growth and molecular functionality of SAMs, we develop a co‐assembled monolayer (co‐SAM) for obtaining efficient hole selection and suppressed recombination at the hole‐selective interface in inverted perovskite solar cells (PSCs). By engineering the position of methoxy substituents, an aligned energy level and favorable dipole moment can be obtained in our newly synthesized SAM, ((2, 7‐dimethoxy‐9 H ‐carbazol‐9‐yl) methyl) phosphonic acid (DC‐PA). An alkyl ammonium containing SAM is co‐assembled to further optimize the surface functionalization and interaction with perovskite layer on top. A champion device with an excellent power conversion efficiency (PCE) of 23.59 % and improved device stability are achieved. This work demonstrates the advantage of using co‐SAM in improving performance and stability of PSCs. Abstract : An efficient hole selection interface with reduced recombination loss is achieved through co‐assembly of a structurally engineered hole‐selective self‐assembled monolayer (SAM) and an ammonium passivator, with which a champion power conversion efficiency (PCE) of 23.59 % and improved device stability are accomplished in inverted perovskite solar cells (PSCs).